Algonquin ethnobotany : An interpretation of aboriginal adaptation in Southwestern Quebec - Black, Meredith Jean (Book collections on Project MUSE., 1980)
Examines the plants used by Algonquin Indians in southwestern Quebec from an ecological and historical point of view.